Characteristics, importance and objectives of research: an overview of the indispensable of ethical research - Islam, Md. Sirajul; Samsudin, Sofiah (International Journal of Scientific and Research Publications, 2020)
This study focuses on Characteristics, Importance and Objectives (CIO) of research. The main aim of this article is to emphasize on research ethics. Knowledge in characteristics, importance and objectives of research motivate to be ethical in research. It is the utmost importance knowing these three basic subjects of research for researchers specially for novice researchers. These improve research mentality, academic attitude and way of thinking that enable researcher to choose research area, generate constructive potential research title. In addition, motivate to know what the problem is and cause of problem and how to solve the recognized valid problem. In fact, an outstanding unique contribution of a research depends on applying research ethics. A profound understanding the (CIO) of research reinforce research motive and enable to follow research ethics that is core requirement in each research activities.